ANALISIS FAKTOR PENYEBAB KESULITAN MENYELESAIKAN SOAL CERITA MATEMATIKA PERSPEKTIF GURU DAN SISWA KELAS IV - Ahmad Fatikhin; Farhan Saefudin Wahid; Dedi Romli Triputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the causes of students' difficulties in solving mathematical story problems based on the perspectives of teachers and fourth-grade students of SDN Slatri 01. The study used a qualitative approach with a descriptive design. The research subjects consisted of fourth-grade teachers and 39 fourth-grade students. Data collection techniques used interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results showed that students' difficulties occurred at the stages of understanding the problem, planning solutions, implementing plans, and re-checking answers. The causative factors came from internal factors such as low reading literacy skills, learning interests, motivation, and student learning habits. External factors included less varied learning methods, limited use of learning media, and a lack of contextual practice problems. Teachers' and students' perspectives showed a similarity that understanding the language of the problem was the main obstacle in solving mathematical story problems. This study provides recommendations for the need for more contextual learning, the use of concrete media, and the habituation of problem-solving strategies according to Polya.